Post a New Question


posted by on .

If f(x)=2x+1/x-3 and g(x)=1-x/2
Show that f(g)(x)=g(f)(x)

  • math - ,

    Before I solve this, clarify if you mean it the way you typed it, or
    if you meant:
    f(x) = (2x+1)/(x-3) or f(x) = 2x + 1/(x-3) or ...
    g(x) = (1-x)/2

  • math - ,

    Hi Reiny,
    I did not get any parentheses with the question. I got it the way I typed it.


Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question